2019
DOI: 10.1021/jacs.9b03910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Properties of Heptabenzo[7]circulene and Octabenzo[8]circulene

Abstract: This study puts forth two new members of fully ortho-benzannulated [n]­circulenes, heptabenzo[7]­circulene and octabenzo[8]­circulene, which are new negatively curved nanographenes and also represent unprecedented structures of septuple [4]­helicene and octuple [4]­helicene, respectively. The successful synthesis of them through Scholl reaction in good to excellent yields takes advantage of the reactivity of naphthalene. Quantum chemistry calculations reveal that heptabenzo[7]­circulene and octabenzo[8]­circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 57 publications
1
101
0
1
Order By: Relevance
“…The half‐life of 6 at room temperature is one day ( t 1/2 =23±1 h). The mechanism for the inversion is similar as has been suggested for the larger [8]circulenes, although the Gibbs free energy for the inversion barriers are much lower (30.5 kJ mol −1 for tetrabenzo[8]circulene and 38.5 kJ mol −1 for octabenzo[8]circulene) . It is in a similar regime as calculated for the grossly warped nanographene by Scott, Itami, and co‐workers (79.1 kJ mol −1 ) .…”
Section: Figuresupporting
confidence: 79%
See 1 more Smart Citation
“…The half‐life of 6 at room temperature is one day ( t 1/2 =23±1 h). The mechanism for the inversion is similar as has been suggested for the larger [8]circulenes, although the Gibbs free energy for the inversion barriers are much lower (30.5 kJ mol −1 for tetrabenzo[8]circulene and 38.5 kJ mol −1 for octabenzo[8]circulene) . It is in a similar regime as calculated for the grossly warped nanographene by Scott, Itami, and co‐workers (79.1 kJ mol −1 ) .…”
Section: Figuresupporting
confidence: 79%
“…Curvature or contortion can be implemented into PAHs by the introduction of cove or fjord regions, even if the PAHs are consisting of six‐membered rings exclusively . Another possibility is the embedding of rings that are deviating in size from the six‐membered one, such as four‐, five‐, seven‐, or eight‐membered rings to cause contortion . With the exception of the four‐membered ring containing PAH, the latter are by far the most rare ones …”
Section: Figurementioning
confidence: 99%
“…It is also worth emphasizing that some very strained products, such as helicenes, bowls and saddles, can be synthesized using this method. Indeed, in contrast to earlier assumptions, the Scholl reaction is capable of proceeding even if ring closure is accompanied by the introduction of significant steric strain that leads to nonplanar molecules . Progress has been particularly impressive in the case of surface‐assisted dehydrogenation, which has enabled the synthesis of nanographenes of unprecedented size by scanning tunneling microscopy …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in contrast to earlier assumptions,the Scholl reaction is capable of proceeding even if ring closure is accompanied by the introduction of significant steric strain that leads to nonplanar molecules. [274,275] Progress has been particularly impressive in the case of surface-assisted dehydrogenation, which has enabled the synthesis of nanographenes of unprecedented size by scanning tunneling microscopy. [169,276] Despite all the impressive progress summarized herein, methods for the oxidative coupling of arenes still have some limitations,which will no doubt be the focus of future studies.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…3 On the basis of this concept, we have recently demonstrated that the Scholl reactions can be facilitated by introducing naphthalene moieties in the substrate leading to highly curved polycyclic aromatics. 4, 5 Herein, we expand the scope of this strategy by showing successful synthesis of an unprecedented aromatic saddle (1 in Scheme 1), which is enabled by including naphthylene groups in the substrate of the Scholl reaction. Aromatic saddles, also known as negatively curved polycyclic arenes, have recently received increasing attention 6,7 for two reasons.…”
Section: Introductionmentioning
confidence: 99%